2020
DOI: 10.1101/2020.03.06.981399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inference and search on graph-structured spaces

Abstract: How do people learn functions on structured spaces? And how do they use this knowledge to guide their search for rewards in situations where the number of options is large? We study human behavior on structures with graph-correlated values and propose a Bayesian model of function learning to describe and predict their behavior. Across two experiments, one assessing function learning and one assessing the search for rewards, we find that our model captures human predictions and sampling behavior better than sev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…This provides a similarity metric based on transition dynamics, where an analytic method for computing the SR in closed form is to assume random transitions through the state space. This assumption of a random policy produces a nearly identical similarity metric as the RBF kernel [76], with exact equivalencies in certain cases [77].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a similarity metric based on transition dynamics, where an analytic method for computing the SR in closed form is to assume random transitions through the state space. This assumption of a random policy produces a nearly identical similarity metric as the RBF kernel [76], with exact equivalencies in certain cases [77].…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, clustering methods (e.g., [79]) can also provide local approximations of GP inference by making predictions about novel options based on the mean of a local cluster. For instance, a related reward-learning task on graph structures [76] found that a k-nearest neighbors model provided a surprisingly effective heuristic for capturing aspects of human judgments and decisions. However, a crucial limitation of any clustering models is it would be incapable of learning and extrapolating upon any directional trends, which is a crucial feature of human function learning [59,60].…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies have shown reliable signatures of generalization and directed exploration in adults, with relatively little random exploration (Wu et al, 2018; Wu, Schulz, Gershman, 2020). In a comparison of children aged 7–11 and adults, Schulz et al (2019) found no age‐related differences in random exploration.…”
Section: Goals and Scopementioning
confidence: 93%
“…An interesting direction for future studies is to combine surprise modulation with more abstract model building algorithms, e.g., for learning the structure of neighborhood relations of an environment in the form of a graph [73,74]. Such algorithms may explain the slight difference between the participants' adaptive behavior and SurNoR's predictions (Fig 6B).…”
Section: Surprise Modulates Learningmentioning
confidence: 99%